2017
DOI: 10.1002/adsc.201701028
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Cooperative Effect of Sodium borohydride‐Iodine Towards Cascade C−N and C−S/Se Bond Formation: One‐pot Regioselective Synthesis of 3‐Sulfenyl/selenyl Indoles and Mechanistic Insight

Abstract: In this work, a new strategy to synthesize 3-sulfenyl/selenyl indole is reported wherein LCÀMS reveals a novel insight into synergistic cooperative effect of NaBH 4 -I 2 which allows cascade CÀN and CÀS/CÀSe bond formations via reduction-nucleophilic cyclization-chalcogenylation, three steps in one-pot, towards regioselective synthesis of diverse 3-chalcogenyl indoles including 5-bromo-3-[(3,4,5-trimethoxyphenyl)thio]-1H-indole, a known lead anticancer compound, directly from 2-amino-phenacylchlorides and thio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Among the numerous types of indolecontaining architectures, indoles bearing CÀ S bond, also known as sulfenylated/sulfonylated indoles, are ubiquitous structural motifs demonstrate enormous biological activities particularly antiviral, anticancer, and antibacterial (Figure 3). [12,[26][27][28][29][30][31][32][33][34][35][36] A recent survey also revealed that pharmaceutical companies are mostly interested in the development of new approaches for the synthesis of biologically privileged sulfur/ nitrogen atom conatining heterocyclic scaffolds. [37][38] In this review, we summarize the development of arylsulfonylated/ sulfenylated indoles for a class of non-nucleoside reverse transcriptase inhibitor (NNRTIs).…”
Section: Reviewmentioning
confidence: 99%
“…Among the numerous types of indolecontaining architectures, indoles bearing CÀ S bond, also known as sulfenylated/sulfonylated indoles, are ubiquitous structural motifs demonstrate enormous biological activities particularly antiviral, anticancer, and antibacterial (Figure 3). [12,[26][27][28][29][30][31][32][33][34][35][36] A recent survey also revealed that pharmaceutical companies are mostly interested in the development of new approaches for the synthesis of biologically privileged sulfur/ nitrogen atom conatining heterocyclic scaffolds. [37][38] In this review, we summarize the development of arylsulfonylated/ sulfenylated indoles for a class of non-nucleoside reverse transcriptase inhibitor (NNRTIs).…”
Section: Reviewmentioning
confidence: 99%
“…Selenofunctionalization results in formation of C−Se bond which is prevelant in organic synthesis with pharmaceutical applications. It has been achieved through different means such as transition‐metal catalyzed coupling/cross‐coupling and addition reactions, [88a,b] iodine‐catalyzed reactions, [88c,d] Ni‐based nanocatalyst assisted regioselective addition reaction [88e] . Selenylated compounds can further act as viable intermediates for further transformations in complex synthetic schemes as witnessed in stereoselective synthesis of nucleosides and nucleotides [88f] …”
Section: Overview On Selenium‐catalyzed/selenium Incorporating Transfmentioning
confidence: 99%
“…Therefore, other routes involving the cascade cyclization/selenylation reactions of various designed 2-amino-containing substrates have attracted more attention. The Sinha group disclosed an NaBH 4 –I 2 -catalyzed protocol for the construction of 3-selenylindoles with amino phenacylchlorides and diaryldiselenide (Scheme b) . Zhou, Larock, and Wang groups independently developed useful strategies for the synthesis of 3-selenylindoles via tandem cyclization of 2-alkynylaniline derivatives with selenylation reagent (Scheme c) .…”
Section: Introductionmentioning
confidence: 99%
“…The Sinha group disclosed an NaBH 4 −I 2 -catalyzed protocol for the construction of 3selenylindoles with amino phenacylchlorides and diaryldiselenide (Scheme 1b). 7 Zhou, Larock, and Wang groups independently developed useful strategies for the synthesis of 3-selenylindoles via tandem cyclization of 2-alkynylaniline derivatives with selenylation reagent (Scheme 1c). 8 However, these approaches lack substrate generality and require harsh conditions, thus rendering them ineffective and impractical.…”
Section: ■ Introductionmentioning
confidence: 99%